Fiber Bragg Grating in Biomedical Application - Moosa, Arwa A. (Al-Nahrain Journal for Engineering Sciences, 2017)
The aim of this work is to use Fiber Bragg Grating (FBG) to detect the breast cancer at its earliest stages based on the Photoacoustic (PA) hybrid technique. The fiber Bragg gratings sensitivity to acoustic wave, effect of grating length, effect of grating refractive index modification, and ultrasonic frequency on the wavelength sensitivity and intensity sensitivity of the ultrasonic sensor (FBG) for ultrasonic waves were investigated using a simulation programs. A wavelength for the photoacoustic (PA) excitation laser was chosen with respect to a high absorption by the tumor and with low absorption to the surrounding tissue (normal tissue); for higher contrast absorption between them. Fiber Bragg can be used as a sensor to detect the acoustic wave emitted from the tumor (depending on the photoacoustic principle). In this study, k-wave a MATLAB toolbox was used to simulate photoacoustic wave which is detected with fiber Bragg grating simulation, using Optisystem program. The acoustic wave was transferred to FBG by using Optisystem-MTLAB communication programs to detect tumors.